Finite-Element Analysis of Keying Process of Plate Anchors in Three-Layer Soft-Stiff-Soft Clay Deposits - Tugen Feng; Huajiao Xu; Jian Song; Jian Zhang; Mi Zhou; Fuhai Zhang (Advances in Civil Engineering)
This paper presents the results from numerical modeling of the keying process of plate anchors in three-layer soft-stiff-soft clay deposits. Three-dimensional large deformation finite-element analyses were carried out, and the results were firstly validated by the centrifuge test data and the previous numerical results. The soil flow mechanism during the keying process of plate anchors was examined, and a series of parametric studies were performed to investigate the factors affecting the rotation characteristics of plate anchors with an emphasis on the presence of the interbedded stiff soil layer. The results indicate that the loss of embedment depth of plate anchors decreases with the increase of the thickness of the first soil layer when the anchor is initially located at the middle of stiff soil layer. The flow velocity of soil around the anchor that is initially embedded at the first layer and adjacent to the underlying interbedded stiff soil layer is generally larger, resulting in a smaller embedment depth loss compared with the traditional normally consolidated soil layer. The interbedded stiff soil layer affects the keying process of plate anchors embedded 1.0B above and 2.0B below the interbedded stiff soil layer (B is the width of the square plate anchors). The increase of the strength of local soil around the plate anchors leads to the increase of the embedment depth loss, but the increase of the strength of soil slightly away from the plate anchors leads to the decrease of the embedment depth loss.